Exploring the Role of Peer Feedback in Enhancing EFL Learners’ English Speaking Fluency and Accuracy - Setiawan, Agus; Rahman, Arif; Jupri, Jupri; Meraj, Mohammed (Journal of Language and Literature Studies, 2025)
The ability to speak fluently and accurately in English remains a central goal for learners in English as a Foreign Language (EFL) contexts. However, limited classroom time and teacher-centered approaches often hinder opportunities for meaningful oral practice. This study investigates the impact of peer feedback as a pedagogical strategy to enhance fluency and accuracy in English speaking among EFL learners. The research aimed to examine not only linguistic development but also the broader cognitive and motivational effects of peer interaction. A mixed-methods design was employed, involving both quantitative and qualitative approaches. The participants were EFL learners who underwent a structured peer feedback intervention. Data were collected through pre- and post-tests, peer feedback forms, classroom observations, and semi-structured interviews. Quantitative analysis revealed statistically significant improvements in both fluency and accuracy after the intervention. Qualitative findings highlighted increased metacognitive awareness, motivation, and active engagement, as learners critically reflected on their performance and collaborated with peers. Notably, gender-based differences in feedback styles added depth to the peer learning dynamic. While the study was limited by its short duration and relatively homogeneous participant proficiency, the findings affirm the effectiveness of peer feedback in promoting oral communication skills. It is concluded that peer feedback fosters learner autonomy and supports linguistic and interpersonal growth. The study recommends incorporating peer feedback into EFL speaking curricula and suggests that future research explore its long-term impacts, involve diverse proficiency levels, and utilize technological tools to optimize feedback practices.